2022
DOI: 10.3390/su142215002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Leisure Agriculture in Xinjiang and Its Influencing Factors Based on Geographically Weighted Regression

Abstract: As a new industry in modern agriculture, leisure agriculture has a strong correlation with rural tourism, and provides rural areas with positive prospects for sustainable development. However, leisure agriculture tends to include a number of bottlenecks. In this study, we investigated the spatial distribution of leisure agriculture in Xinjiang, and the factors that affect it. Kernel density analysis, the nearest-neighbor index, and the geographic concentration index were used to analyze the distribution charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Human activities can either hasten or slow down the pace of ecosystem degradation or recovery, contingent upon natural factors [78]. Given Xinjiang's unique natural and geographical characteristics, population distribution varies significantly [79], with most regions characterized by low population densities and sensitive, fragile ecosystems. A moderate increase in population might support ecological projects and improve ecological quality.…”
Section: Analysis Of Driving Factors Of the Fvc Spatial Patternmentioning
confidence: 99%
“…Human activities can either hasten or slow down the pace of ecosystem degradation or recovery, contingent upon natural factors [78]. Given Xinjiang's unique natural and geographical characteristics, population distribution varies significantly [79], with most regions characterized by low population densities and sensitive, fragile ecosystems. A moderate increase in population might support ecological projects and improve ecological quality.…”
Section: Analysis Of Driving Factors Of the Fvc Spatial Patternmentioning
confidence: 99%
“…Thus, an imbalance is created for the constant formation and realization of economic interests at all levels of the economic system -from micro (Chang et al, 2022;Zhu et al, 2022) to macro (Ferreira et al, 2020) and mega levels (Ivancsóné et al, 2018). Chang et al (2022) indicate that rainfall and population size have a greater differential effect on rural tourism's spatial distribution than transport, tourism resources, and urban factors. Zhan et al (2022) identified four key aspects: national development strategy, social environment, geographical environment and historical development.…”
Section: Analysis Of the Territorial Unevenness Of The Tourism Market...mentioning
confidence: 99%
“…The abovementioned components can interact within a constrained area in more extensive settings. While more people are discovering and enjoying the benefits of rural vacations and recreational agriculture, challenges remain in the design, planning, building, and ongoing growth of exploring agrarian parks [8] -the issues like landscape homogenization and iconic landscape deficiency. There is a proliferation of tourist agricultural park initiatives, all essentially the same [9].…”
Section: Introductionmentioning
confidence: 99%